Expressão da proteína Ki-67 e da glicoproteína MUC1 em carcinomas mucoepidermóide de glândulas salivares menores - GONÇALVES, Cintia Ferreira (2009)
Aims: Investigate the prognostic significance of cellular proliferation indexes and mucosecretional activity in Mucoepidermoid Carcinoma (MEC) of oral cavity minor salivary glands using the immunoexpression of the protein Ki-67 and the glycoprotein MUC1 in young people and adults, by correlating these markers to clinical and pathological parameters. Material and methods: From 1987 to 2007, 35 cases of MEC were diagnosed in minor salivary glands. Demographic clinical data were obtained from clinical records, the microscopic diagnosis was revisited and the specimens were reclassified in terms of histologic grading, according to the system used by Batsakis & Luna (1990). Qualitative and quantitative analyses of the expression of Ki-67 protein and MUC1 glycoprotein, obtained through immunohistochemistry, were correlated to the variables: age, gender and histologic grading. Results: The cases of MEC (n=35) were more frequently found in people over thirty (60%), with predilection for females (1.7:1) and occurred most frequently in the hard palate (54.3%). Of the cases studied, 42.9% were low grade, 37.1% intermediate and 20% high grade. A greater expression of Ki-67 was found for adults while the greater expression for young people was MUC1, although neither result was statistically significant (Ki-67 / P=0.44 e MUC1 / P=0.5). In addition no prognostic relation was seen between male and female, despite the greater expression of both markers for males (Ki-67 / P=0.58; MUC1 / P=0.4). In terms of histologic grading intermediate and high grade tumors presented a greater expression for both markers, but without any statistical significance (Ki-67 / P=0.18; MUC1 / P=0.6). Conclusions: MEC in minor salivary glands could present a tendency of lesser aggressiveness in younger patients when compared to adults; in females when compared to males, and in tumors of low histologic grade when compared to those of intermediate or high grade. Furthermore, this tumor may have a tendency to higher mucossecretory activity in young than in adults, in males than in females and in intermediate and high grade tumors.